Desain Pengembangan Kurikulum Pembelajaran Bahasa Arab pada Tujuan Khusus Pemandu Wisata (Tour Guide) - Irvan Maulana Tamsil (Alsina : Journal of Arabic Studies, 2019)
Language Arabic, which has now become an international language, has a big contribution in developing science. This Tern shows the existence of active Arabic communication with the languages that exist in this world. By using a language that is understood together, one can establish social relations in the community. The purpose of this study is to design Arabic learning curriculum development specifically for the purpose here of tourism as a tour guide. This research method used library research. The results of the research show that the design learning of Arabic curriculum development is a special purpose tour guide, a tour guide is more, able, fluent and professional in communicating Arabic and knows the ins and outs of the world of tourism, as well as the destination when dealing with tourists from the Middle East.